Methods of Work on Different by Linguistic Nature Writings in the Context of Professional Forming of Philologists - Yavorska, Stefaniia (Pedagogical Discourse, 2017)
The article is devoted to the issue of formation of spelling skills of secondary school’s students. Special researches show a low literacy of schools’ graduate students, and their knowledge and skills still have a lot of gaps. Majority not enough learns theoretical material. Besides, they don’t see orthograms and can not find them. The main reason should be seen primarily in misunderstanding of the linguistic nature of writing by students, in the selection of ineffective teaching methods and techniques. The purpose of the article: to justify the choice of methods and techniques for mastering spelling skill, the ways of mastering different linguistic nature writing. Objective: to analyze the scholars’ views about the features of formation of spelling skills; to identify the conditions effective spelling principles’ relationship; to highlight effective methods and techniques of teaching. According to the objectives highlighted the views of psychologists, pedagogues and methodologists to develop competent writing. Different approaches to the formation of spelling skills were considered, their heterogeneity was proven. Since the spelling reflects phonetic and morphological system of Ukrainian language, to consider the principles of spelling is important for its understanding. The ways of processing of different linguistic nature orthograms were justified, conditions of interconnection of spelling principles, effective methods and techniques of teaching. Were defined methodology of phonetic assimilation of writing: production of highly students’ phonemic hearing; correct, precise pronunciation of sounds; understanding of the word’s meaning (bogatyr - bogatyr); words’ phonetic analysis; improving skills to match a certain sound with the appropriate letter, i.e. comparison of pronunciation and spelling; exercises on the selection of certain words orthograms. Morphological writing require the application of rules, active mental analytic-synthetic activity of students and to provide morphemic and word’s building analyzing of word, to do different types of dictations, translations, essays etc.. Effective methods of processing orthograms that traditionally written – remembering, various kinds of decommissioning, work with special spelling worksheets, guides and etc. Orthograms, which are explained with the semantic principle, need an analysis of meanings shades, understanding the meaning of speech in general. It is concluded that mastering spelling is impossible to limit of only one way. The study of different linguistic nature arthograms requires a differentiated approach, the use of methods and techniques that take into account the nature of writing (phonetic, morphological, differentiating and historical). Teacher’s understanding of the spelling language system can help accurately to set specific tasks in the handling of certain spelling topics, to provide existing difficulties, to understand the causes of various errors which are made by the students and find ways to prevent and correct them. For students-philologists, teachers of Ukrainian schools of different types. Key words: Ukrainian orthography, spelling skills, methods and techniques of teaching, linguistic nature of spelling, spelling principles, spelling skill, differentiation.